Community dance and youth empowerment in Uganda - Wang, Wenxi (2017)
This study documented the ideologies and strategies used by community dance organization to empower youth and revealed youth experience in such project. The whole research employed a qualitative approach. The Breakdance Project Uganda (BPU), which had provided free breakdance classes to disfranchised youth for more than 10 years, was selected as the study case. Thirteen youth aged from 15-30 who had been participated in BPU for more than 1 year were recruited in in-depth interviews and focus group discussions using a purposive sampling approach, one BPU facilitator was interviewed about the strategies and ideologies of the project. Recordings of interviews and focus group were transcribed in a denaturalized way and analyzed in a thematic approach. The participant observation note also worked to compensate the data of the research. In general, the study revealed that community dance project had a positive impact on lives of youth, especially those who had stayed longer. Dancing as an expressive performing art improved their self-esteem. The dance community provided a safe and resourceful place for youth to explore and develop themselves. Thus community dance project provided chance for youth to be empowered socially and economically. Besides the youth also gained potent sense of self, developed more skills and competences, and raised critical awareness about themselves and the environment. Eventually youth were more able to control over their lives. However there were also challenges in terms of time and transportation expense for youth to attend the dance session, also there could be sub-groups in such project that brought negative impact on youth. Moreover the society especially parents usually held negative image of such dance group thus stopped their children from participation.